2012
DOI: 10.1097/fbp.0b013e328356c3ac
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a multicomponent behavioral intervention on impulsivity and cognitive deficits in adolescents with excess weight

Abstract: The aim of this study was to explore the effects of a multidisciplinary behavioral intervention including cognitive behavioral therapy, structured physical activity, and dietary counseling on impulsive personality and cognitive skills and subsequent BMI loss in excess weight adolescents. Forty-two adolescents with excess weight (14 males and 28 females, range 12-17 years), as defined by the International Obesity Task Force Criteria, participated in our study. We used a longitudinal observational design with tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 0 publications
4
27
1
Order By: Relevance
“…Studies specifically targeting adolescents reported reductions in BMIz ranging from 3 to 4% to 9% at intervention end which was similar to those studies targeting the whole family (range 2% to 9% ). Online‐only programs which did not involve any face‐to‐face sessions had somewhat smaller reductions in BMI (between 1% and 2–4% ) compared with face‐to‐face only programs (1% to 7% ), and those which involved technology in addition to face‐to‐face sessions (reductions in BMIz; 2% to 4% End‐I, 3–4% to 9–10% FU) did not appear to be more effective than those without technology (reductions in BMIz; 5% to 9% End‐I; 8–12% to 16% at FU). Program length and study quality did not appear to be associated with weight management outcomes.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…Studies specifically targeting adolescents reported reductions in BMIz ranging from 3 to 4% to 9% at intervention end which was similar to those studies targeting the whole family (range 2% to 9% ). Online‐only programs which did not involve any face‐to‐face sessions had somewhat smaller reductions in BMI (between 1% and 2–4% ) compared with face‐to‐face only programs (1% to 7% ), and those which involved technology in addition to face‐to‐face sessions (reductions in BMIz; 2% to 4% End‐I, 3–4% to 9–10% FU) did not appear to be more effective than those without technology (reductions in BMIz; 5% to 9% End‐I; 8–12% to 16% at FU). Program length and study quality did not appear to be associated with weight management outcomes.…”
Section: Resultssupporting
confidence: 74%
“…Study, program and participant characteristics are reported in Table . Half of the programs were from the United States (US; n = 11) with the remainder from Europe ( n = 7) , Australia ( n = 2) and the United Kingdom (UK; n = 1) . The programs were evaluated as controlled trials ( n = 15), both randomized ( n = 10) and non‐randomized ( n = 5) , and as pre–post case series ( n = 6) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Emerging evidence has linked obesity in children and adolescents to lower brain grey and white matter volume in brain regions associated with cognitive control and learning when compared to children and adolescents with healthy weight (Alarcón 2016; Alosco 2014; Kennedy 2016; Maayan 2011; Ou 2015; Yau 2014). This suggests a direct association between obesity and reduced cognitive and academic abilities, and is consistent with findings from animal models where manipulation of fat mass has been shown to affect cognition, probably as a result of inflammatory mechanisms.…”
Section: Introductionmentioning
confidence: 99%